The Deferences of Xylitol Chewing Gum and Mouthwash on Xerostomia in Chronic Renal Failure Patients - Hendra Adi Prasetya; Ratna Sitorus; Lestari Sukmarini (Global Health Science Group, 2020)
Increased blood urea or uremic levels often experienced by patients with Chronic Renal Failure can lead to decreased salivary secretion and xerostomia. Xerostomia is a common symptom of difficulty in chewing, swallowing, decreased taste, speaking, increased oral mucosal lesions, and limited tolerance of dentures. This problem will have an impact on increasing thirst sensations that affect the patient to increase fluid intake that leads to an increase Interdialytic Weight Gain and lead to decreased Quality of Life patients. The aim of this research was to know the effect of chewing gum xylitol and mouthwash on xerostomia in chronic renal failure patients. The design was quasi experiment involving 30 respondents selected by consecutive sampling technique and divided into two groups. Xerostomia measured four times in each session of hemodialysis. The results of study showed there was no differences in the four xerostomia measurements in both intervention groups with p-value> 0.05. However, it is seen from the patient's development chart that the xylitol gum intervention reduced xerostomia faster than the mouthwash intervention. The conclusion of this research was xylitol chewing gum and mouthwash had same effect to reduce xerostomia in patients with chronic renal failure. The results of this study can be recommended to be applied as an intervention to resolve xerostomia in chronic renal failure patients.